Understanding the neuroinflammatory response following concussion to develop treatment strategies - Patterson, Zachary R.; Holahan, Matthew R. (Frontiers in Cellular Neuroscience, 2012)
Mild traumatic brain injuries (mTBI) have been associated with long-term cognitive deficits relating to trauma-induced neurodegeneration. These long-term deficits include impaired memory and attention, changes in executive function, emotional instability and sensorimotor deficits. Furthermore, individuals with concussions show a high co-morbidity with a host of psychiatric illnesses (e.g. depression, anxiety, addiction) and dementia. The neurological damage seen in mTBI patients is the result of the direct impact and mechanical injury, followed by a delayed neuroimmune response that can last hours, days and even months after the injury. As part of the neuroimmune response, a cascade of pro- and anti-inflammatory cytokines are released and can be detected at the site of injury as well as subcortical, and often contralateral, regions. It has been suggested that the delayed neuroinflammatory response to concussions is more damaging then the initial impact itself. However, evidence exists for favourable consequences of cytokine production following traumatic brain injuries as well. In some cases, treatments that reduce the inflammatory response will also hinder the brain's intrinsic repair mechanisms. At present, there is no evidence-based pharmacological treatment for concussions in humans. The ability to treat concussions with drug therapy requires an in-depth understanding of the pathophysiological and neuroinflammatory changes that accompany concussive injuries. The use of neurotrophic factors (e.g. nerve growth factor) and anti-inflammatory agents as an adjunct for the management of post-concussion symptomology will be explored in this review.